أثر صياغة القاعدة الفقهية على تطبيقاتها ومستثنياتها -قاعدة اليقين أنموذجا - بن عزوز, عبد القادر; بوقطيط, الأزهر (جامعة الوادي - University of Eloued, 2022)
إن المتتبع للقواعد الفقهية يجد اختلافاً عند الفقهاء في بعض تطبيقات ومستثنيات نفس القاعدة، وهذا له أسباب عدة؛ ولعل من أهم هذه الأسباب هو موضوع هذا البحث الموسوم بـ "أثر صياغة القاعدة الفقهية على تطبيقاتها ومستثنياتها - قاعدة اليقين أنموذجاً-" وبينت -بعون الله تعالى- الأثر البالغ لصياغة القاعدة الفقهية على تطبيقاتها ومستثنياتها، من خلال اهتمام العلماء بصياغة القاعدة؛ وهذا ما يظهر جلياً عند ترجيحهم لصياغةٍ على أخرى؛ كترجيحهم لصياغة قاعدة النية "إنما الأعمال بالنيات" بهذا اللفظ -وهو لفظ من أوتي جوامع الكلم صلى الله عليه وسلم- على باقي الصيغ. وكتعبير علماء المالكية على قاعدة اليقين بلفظ "الأصل طرح الشك" بدل الصيغ الأخرى؛ فيدخل تحت هذه الصياغة ما انتُقِد على المالكية من عدم دخول بعض الفروع الفقهية تحت تطبيقاتها، لتصبح قاعدة اليقين بتعبير المالكية بنفس مستثنيات القاعدة عند غيرهم، فيتساوى عندئذ كل العلماء في العمل بأصل القاعدة كما سيأتي ذكر إجماعهم على ذلك Abstract : The follower of jurisprudence'rules, one finds difference in some of the applications and exceptions of the same rule, and this has many reasons; the most important of them is the topic of this research '' The importance of formulating the rule of jurisprudence on its applications and exceptions : The principle of certainty as a paradigm''. And showed with –God help- the prominent influence of formulating the rule jurisprudence on its applications and exceptions and according to scientists interest in formulating the rule and this seems clear in weighting one formulation to other : weighting the formulation of intention '' deeds are not but intentions'' This word –the word of the prophet -p.b.u.h- to others . And as the expression of Malikia scientists on the rule of certainty '' the rule is denouncing doubt'' instead of other formulations; so comes under this rule what was Malikia criticized for not entering the other branches of jurisprudence under their application . Thus, the rule of certainty becomes in Malikia expression as the exception of the rule for others, these for all scientists will be equal in taking the origin of the rule as their consensus mentioned before.
مقال
Keywords: القاعدة الفقهية ; قاعدة اليقين ; الأصل طرح الشك ; تطبيقات القاعدة ; مستثنيات القاعدة